VCabral1134
  • VCabral1134
Help me plz will fan and medal! Write a recursive rule for the sequence. a^n = −9+ 2n a. a^1 = −9,a^n = a^n − 1 − 9 b. a^1 = −9,a^n = a^n − 1 + 2 c. a^1 = −7,a^n = a^n − 1 − 9 d. a^1 = −7,a^n = a^n − 1 + 2
Mathematics
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

VCabral1134
  • VCabral1134
I eliminated C and D.
Saurabh135
  • Saurabh135
d is the correct answer
VCabral1134
  • VCabral1134

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Saurabh135
  • Saurabh135
see if we put n=1 in above equation, then a^1 will be equal to -9+2*1 = -7
Saurabh135
  • Saurabh135
and if we put n-1 instead of n in above equation then a^n-1 = -9 + 2*(n-1) = -9 + 2n -2 and subtracting these equations we get a^n - a^n-1 = 2 which implies a^n = a^n-1 + 2

Looking for something else?

Not the answer you are looking for? Search for more explanations.